Hematological characterization of Astronotus ocellatus (Cichliformes: Cichlidae): Species of economic importance in the Peruvian Amazonia - Gonzales Flores, Anai (2020)
The aim of this study was to characterize the hematological parameters of Astronotus ocellatus and to determine possible correlations between variables. Blood samples were collected from 15 specimens (weight: 109.43 ± 22.9 g, total length: 15.43 ± 1.28 cm), kept in concrete tanks and fed with a commercial diet extruded at 42% crude protein. Blood samples were collected by puncture of the caudal vessel using syringes with EDTA (10%). The erythrocytic values were: haematocrit 24.5 ± 1.2%, haemoglobin 8.8 ± 2.4 g/dl; erythrocytes 1.10 ± 0.10 x 106/μl, MCV 222.1 ± 41.0 fl, MCHC 36.7 ± 10.4 g/dl. Leukocyte parameters were total leukocytes 7.3 ± 2.6 x103/μl, lymphocytes 67.3 ± 7.6%, monocytes 4.13 ± 1.4%, eosinophils 27.5 ± 8.9%, neutrophils 1.08 ± 1.3%. In serum biochemistry: total protein 3.44 ± 1.1 g/dl, glucose 64.39 ± 28.8 mg/dl, cholesterol 253.4 ± 91.2 mg/dl. Positive correlation was observed between haemoglobin and MCHC. Also, negative correlation between bodyweight and body length with the number of erythrocytes. The values found are within the range reported for this fish species.